Hypothermia Reduces Mortality, Prevents the Calcium Plateau, and Is Neuroprotective Following Status Epilepticus in Rats - Phillips, Kristin F.; Deshpande, Laxmikant S.; DeLorenzo, Robert J. (Frontiers in Neurology, 2018)
Status Epilepticus (SE) is a major neurological emergency and is considered a leading cause of Acquired Epilepsy (AE). We have shown that SE produces neuronal injury and prolonged alterations in hippocampal calcium levels ([Ca2+]i) that may underlie the development of AE. Interventions preventing the SE-induced Ca2+ plateau could therefore prove to be beneficial in lowering the development of AE after SE. Hypothermia is used clinically to prevent neurological complications associated with Traumatic Brain Injury, cardiac arrest, and stroke. Here, we investigated whether hypothermia prevented the development of Ca2+ plateau following SE. SE was induced in hippocampal neuronal cultures (HNC) by exposing them to no added MgCl2 solution for 3-h. To terminate SE, low Mg2+ solution was washed off with 31°C (hypothermic) or 37°C (normothermic) physiological recording solution. [Ca2+]i was estimated with ratiometric Fura-2 imaging. HNCs washed with hypothermic solution exhibited [Ca2+]i ratios, which were significantly lower than ratios obtained from HNCs washed with normothermic solution. For in vivo SE, the rat pilocarpine (PILO) model was used. Moderate hypothermia (30-33°C) in rats was induced at 30-min post-SE using chilled ethanol spray in a cold room. Hypothermia following PILO-SE significantly reduced mortality. Hippocampal neurons isolated from hypothermia-treated PILO SE rats exhibited [Ca2+]i ratios which were significantly lower than ratios obtained from PILO SE rats. Hypothermia also provided significant neuroprotection against SE-induced delayed hippocampal injury as characterized by decreased FluoroJade C labeling in hypothermia-treated PILO SE rats. We previously demonstrated that hypothermia reduced Ca2+ entry via N-methyl-D-aspartate and ryanodine receptors in HNC. Together, our studies indicate that by targeting these two receptor systems hypothermia could interfere with epileptogenesis and prove to be an effective therapeutic intervention for reducing SE-induced AE.